The church and the ministry in the early centuries the eighteenth series of the Cunningham Lectures - Lindsay, Thomas Martin, 1843-1914; Cunningham lectures (London, UK Hodder and Stoughton, 1910)
Includes index.
Keywords: Church history -- primitive and early church, ca 30-600.